The Deterrence Effect of Whistleblowing: An Event Study of Leaked Customer Information from Banks in Tax Havens - Niels Johannesen; Tim Stolper (Center for Economic Studies and ifo Institute (CESifo), 2017)
We document that the first leak of customer information from a tax haven bank caused a sudden flight of deposits from tax havens and a sharp decrease in the market value of banks known to be assisting with tax evasion. The loss of market value was largest for the banks most strongly involved in tax evasion and zero for banks with no known ties to tax evasion. Subsequent leaks had qualitatively similar although smaller effects. Our findings suggest that whistleblowing in tax haven banks deters offshore tax evaders by increasing the perceived risk of committing and assisting with tax evasion.
Keywords: G21; H26; K42; 330; whistleblowing; economic crime; tax evasion; tax havens